Uberization Political Economy: Worker Exploitation Regarding Three Forms of Work Intermediation in Platform Companies - Franco, David; Ferraz, Deise Luiza; Ferraz, Janaynna de Moura (Organizações & Sociedade, 2023)
A wide range of studies has emerged on the precariousness of uberized jobs. Nonetheless, there is a gap regarding how these precarious jobs are integrated into the global movement of private valuation and appropriation of the workforce. Thus, this essay aims to apprehend the movement of capital reproduction whose material base occurs in the digital platform dynamics, demonstrating the different forms of intermediated work engendered in the global accumulation process. Using a historical materialist approach, we analyze the phenomenon of uberization in the expansion movement of the production and circulation of goods, scrutinizing the dynamics of big platform companies regarding their relationship with workers and customers, revealing mediations in the movement of values, which culminates in three forms of labor intermediation: (a) Form 1: as a commodity for individual consumption; (b) Form 2: as part of the work processes of industrial capital; and (c) Form 3: as a moderator of exchange relationships. We conclude by indicating that the three forms of uberized products help us to understand how this commodity production process submits men and women to precarious working conditions and increased exploitation. Furthermore, forms 2 and 3, which are more complex and mediated, demonstrate how uberization spreads across the production chain and facilitates the extraction and attraction of surplus value elsewhere, denoting the imperialist character of capitalist dynamics today.